Species composition and structure of degraded mangrove vegetation in the Air Telang Protected Forest, South Sumatra, Indonesia - SYAIFUL Eddy; MOH. RASYID RIDHO; ISKHAQ ISKANDAR; ANDY MULYANA (Society for Indonesian Biodiversity, 2019)
Abstract. Eddy S, Ridho MR, Iskandar I, Mulyana A. 2019. Species composition and structure of degraded mangrove vegetation in the Air Telang Protected Forest, South Sumatra, Indonesia. Biodiversitas 20: 2119-2127. Air Telang Protected Forest (ATPF) is one of the protected forests in the coastal area of South Sumatra, Indonesia which is around 12,660.9 hectares. This area is strategic because it borders directly with the Bangka Strait and adjacent to Sembilang National Park making it easy to access by the community. Various anthropogenic activities in the region such as residential, farming, agriculture, aquaculture, port and timber harvesting have led to degradation and loss of primary mangrove forest. This study aims to analyze the species composition and community structure of mangrove vegetation in the ATPF. The data were collected through observations at several point-centered samplings which were used to analyze the species composition and community structure of the vegetation and the physicochemical conditions of the environment. The species composition of this area consists of 20 species belonging to 14 families. The dominant species of tree, sapling and seedling stages are Nypa fruticans, Rhizophora apiculata and Acrostichum aureum, respectively. Overall species diversity index in this region is classified as very low, ranging from 0.00 to 0.73. Cluster analysis showed three types of vegetation structures in this region, namely Cyperus-Acrostichum type (shrub vegetation), Acrostichum-Rhizophora type (secondary forests) and Nypa-Avicennia (primary forests).